Statutes of the Colegio Seminario Consiliar de San Luis, Ecuador - Colegio Seminario Consiliar de San Luis (Ecuador)
Volume (40 pages) containing statutes of the Colegio Seminario Consiliar de San Luis, Ecuador.
Collection material in Spanish.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ecuador -- History -- 1830-1895.